Effects of Lotus (Nelumbo nucifera Gaertn.) on the Methane Emission in Littoral Zones of a Subtropical Lake, China - Wenchang Zhou; Xiangjuan Yuan; Liangkang He; Yuhu Shi; Xiuhuan Xu; Wenhui Ou; Shanshan Xiang; Jiawei Yang; Tian Fu (Applied Sciences, 2023)
Freshwater lakes represent a potential source of methane (CH4) emission into the atmosphere. However, the CH4 emission contribution to the total emission in the littoral zones of lakes, especially emergent macrophytes (e.g., lotus), is poorly known. Lotus has been cultivated in almost all provinces in China; it is not only an aquatic plant, but also a kind of vegetable. In this study, two sampling zones (lotus plant and open water) were established in the lake of the middle reaches of the Yangtze River. The CH4 emission was measured using a floating opaque chamber and gas chromatography between April and December in the years 2021 and 2022. The results indicated that the flux of CH4 emissions ranged from 0.10 to 59.75 mg m−2 h−1, with an average value of 5.61 mg m−2 h−1, in the open water, while ranging from 0.19 to 57.32 mg m−2 h−1, with an average value of 17.14 mg m−2 h−1, in the lotus plant zone. The maximal CH4 emissions occurred in July and August for the open water, which was highly related to the air and water temperature, whereas it happened in September for the lotus plant zone, possibly due to the high vegetation biomass, indirectly enhancing the high soil organic carbon content, plant-mediated CH4 emission, as well as the lower dissolved oxygen concentration, thus strengthening the production and emissions of CH4. Considering the carbon emissions (both CH4 and CO2) and plant productivity, although greater CH4 emission occurred in the lotus plant zone, it could still represent a potential carbon sink (213 g m−2 yr−1) compared to the open water.